Obesity, metabolic syndrome: sexual and reproductive functions - Bar-Andziak, Ewa (Przewodnik Lekarza/Guide for GPs, 2012)
Most important mechanisms resulting from excessive activity of adipocytes in patients obese and with metabolic syndrome are discussed. Abnormalities in sex steroid metabolism, deranged activity of proinflammatory cytokines and adipokins and insulin resistance influence negatively reproductive system in both sexes. It concerns onset and course of puberty, later gonadal function, fertility and sex life. In pregnant woman massive obesity is a risk factor for complications in mother and baby both during pregnancy and after childbirth. Life style modifications and other methods resulting in decrease of fat tissue component may positively influence mentioned above complications.